Skin reaction patterns as a warning sign for SARS-CoV-2. - Alpalhão, M.; Filipe, P. (European Journal of Pediatric Dermatology, 2020)
Dear Sir, medical doctors are being requested worldwide to fight the current SARS-CoV-2 pandemic. This insidious enemy still has an enormous advantage over us, as asymptomatic or paucisymptomatic individuals can transmit the virus, and thus perpetuate the disease. (...)